2021
DOI: 10.1088/1757-899x/1090/1/012036
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Pollution from Hospital Waste Incinerators: A Case Study from Al-Muthanna Province, Iraq

Abstract: Waste incineration (WI) is the most popular method of hospital waste (HW) disposal in many developing countries. Most hospitals generate large quantities of toxic and persistent waste, which are managed by burning in incinerators. Basically, high concentrations of heavy metal in the food chain are generated from ash residue after burning process. As a result, these concentrations lead to harmful effects on the public health as well as environment. This study aims to investigate the concentrations of heavy meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 23 publications
0
0
0
Order By: Relevance
“…Also, hospital solid waste has been reported to comprise of heavy metals such as Cd, Zn, Pb and Cu. A recent study by Selman and coauthors [6] had shown presence of high concentrations of heavy metal in the ash of incinerated waste from hospital in Iraq. Such kinds of waste material when dumped into soil, get accumulated in the environment as they are non-biodegradable [7].…”
Section: Highlightsmentioning
confidence: 99%
“…Also, hospital solid waste has been reported to comprise of heavy metals such as Cd, Zn, Pb and Cu. A recent study by Selman and coauthors [6] had shown presence of high concentrations of heavy metal in the ash of incinerated waste from hospital in Iraq. Such kinds of waste material when dumped into soil, get accumulated in the environment as they are non-biodegradable [7].…”
Section: Highlightsmentioning
confidence: 99%